Reality of radiological examinations with patients with physical limitations - Katia Elisa Prus Pinho; Rita Zanlorensi Visneck Costa; Roberta Aumann; Joao Henrique Hamann (Brazilian Journal of Radiation Sciences, 2025)
This article discusses the problems faced in daily hospital and clinical practice in Brazil, where there are no examination protocols or bibliographies that professionals can use as a basis for performing radiological examinations on patients with movement limitations and clinical conditions, such as paraplegia and tetraplegia. The objective of this study was to develop a booklet of adaptations of radiological positions for patients with reduced mobility. This material can improve and optimize the services provided in the area, offering greater radiological safety to both the professional and the patient during the examinations. The methodology used involved national bibliographic reviews, technical visits and hospital monitoring, as well as discussions with professionals specialized in the area of ​​radiology, in order to consolidate a more concrete and specific basis for the studied content. Based on these data, it was possible to formalize a simplified booklet, in Portuguese and English versions, accessed through specific QR Codes. The booklet includes some adaptations of radiological examination positions for patients with physical limitations or reduced mobility. The booklet contains a didactic structure for quick consultation to better guide the professional regarding the performance of the examinations. It contains a cover, a presentation, a summary, an introduction, a summary of conventional exams, the adaptation of exams, the conclusion and finally the references. The conclusion of the study emphasizes the importance of expanding research aimed at adapting radiological exams for patients with physical limitations or reduced mobility. These adaptations aim not only at the well-being of the patient, but also at the health, radiological protection and ergonomic safety of professionals, avoiding injuries during the conduct of the exam or its repetition. It is hoped that this material can provide a more humanized  environment for both patients and professionals.